Relationship Between Entrepreneurial Process and Success of Business of Entrepreneurs with Disability in Western Kenya, Kenya - Ojijo Nyabola Thomas; Fredrick Aila; Bando Christine (European Scientific Journal, ESJ, 2019)
Anchored on Empowerment theory, the study adopted a crosssectional research design on the Relationship between entrepreneurial process and success of business of entrepreneurs with disability in Western Kenya, Kenya. The target population was 73 registered businesses of entrepreneurs with disability. Saturated sampling was used in this study. The respondents were 69 business owners, out of which 4 were used for piloting, being 5-10% of sample size considered as a sufficient representation. Primary data were collected using structured questionnaires while secondary data were obtained through document review. The findings revealed that Entrepreneurial processes significantly contributed to business success (β=.609, t(69)=6.285, p=.000) and accounted for 37.1% change in business success (R 2=0.371, F(1,67=39.496, p=.000. The study concluded that an increase in entrepreneurial processes and procurement affirmative action practices will lead to improved business success. The study recommends that entrepreneurship stakeholders and the government assist in improving procurement practices for the persons with disabilities so as to help them improve on their businesses. The study is expected to inform policy makers both entrepreneurship stakeholders and the government on how entrepreneurial process can be used as a tool in improving persons with disabilities access to procurement opportunities and how to empower them.